Pengaruh Harga Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Coffee Kangen Di Kota Bitung - Warouw, Savira Salome; Pangemanan, Lyndon Reindhart Jacob; Pakasi, Caroline Betsi Diana (Sam Ratulangi University, 2024)
This research aims to investigate the influence of price and service quality on customer satisfaction at Coffee Kangen in Bitung City, both partially and simultaneously. The study was conducted from August to October 2023. Respondents were selected through purposive sampling, specifically targeting individuals who had visited Coffee Kangen in Bitung City. The data utilized included both primary and secondary data. Primary data were collected through questionnaires distributed to visitors, employing the slovin method, resulting in a total of 35 respondents. Secondary data were obtained through observations and the profiling of Coffee Kangen. Data analysis techniques involved validity testing, reliability testing, normality testing, multicollinearity testing, heteroskedasticity testing, linearity testing, multiple linear regression, T-test, F-test, correlation coefficient testing, and determination coefficient testing. The statistical analysis was performed using SPSS version 26. The research findings revealed that, partially: 1) Price significantly influences customer satisfaction, and 2) Service quality significantly influences customer satisfaction. Furthermore, simultaneously: Price and service quality together significantly impact customer satisfaction.